Calculation of risk costs in construction projects: Empirical analysis of construction risks applying the Monte Carlo method. Issue 3 (18th September 2019) - Brokbals, Stefanie; Wapelhorst, Vincent; Čadež, Ivan
Abstract: As early as 1971, Schubert made a first contribution to the consideration of risks during the execution of construction projects. In addition to that, he was first to introduce elements of the risk management process to the construction management literature in Germany. By the use of an empirical study of the probability of risk occurrence and the cost amount by risk occurrence, Schubert made among others a statement about the importance of the risks depending on the amount of the risk costs. In an updated study for building construction projects with construction costs ≤2.5 million € and unit price contracts applying the VOB/B primarily the altered risk evaluations are shown; it needs to be emphasized that the sum of the determined risk costs corresponds to Schubert's results. Furthermore, with a variation of the characteristic attributes (response options) of the probability of risk occurrence and the cost amount by risk occurrence, it can be displayed that the risk costs during the execution of building construction projects are even considerably higher. Additionally, a probabilistic risk cost calculation — applying the Monte Carlo method — is used to reveal the bandwidth of risk costs. It can be pointed out that the risk costs range between 2.71% and 8.67% of the construction costs. The results could serve as a benchmark for contractors during the tender calculation to determine the amount of risk costs depending for example, on the market situation, the company‐specific risk disposition as well as strategic considerations.